Vector mesons within nonlocal chiral quark models for strong interactions - Izzo Villafañe, María Florencia (2016)
We analyze meson properties within an SU(2) chiral quark model that includes nonlocal four fermion couplings with wave function renormalization. Model parameters are determined from meson phenomenology, considering different nonlocal form factor shapes. We concentrate in the description of basic features of nonstrange vector and axial vector mesons, considering nonlocal form factors that are based in lattice QCD results for effective quark propagators.